2018
DOI: 10.1002/nau.23838
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year follow‐up on 68 patients with a new post‐operatively adjustable long‐term implant for post‐prostatectomy stress incontinence: ProACT™

Abstract: Aims: This paper presents 4-year follow-up results for patients enrolled in a pivotal study conducted to support an FDA premarket approval application (PMAA). The study evaluated the safety and efficacy of the ProACT Adjustable Continence Therapy for the treatment of post-prostatectomy stress urinary incontinence (SUI). Methods: The clinical study involved 11 clinical sites and enrolled 160 subjects, all male. A total of 124 subjects met study criteria and 123 were implanted with ProACT. Baseline and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…The success rates in the Nestler study, defined as <50% improvement, for 63 patients with one revision were 77.8% compared with a success rate of 82.6% for the entire cohort (N = 134). Similar results were found by Nash et al, showing a success rate of 77.3% for the 22 patients who were explanted and re‐implanted compared to a success rate of 80.9% for the entire cohort (N = 68).…”
Section: Discussionsupporting
confidence: 87%
“…The success rates in the Nestler study, defined as <50% improvement, for 63 patients with one revision were 77.8% compared with a success rate of 82.6% for the entire cohort (N = 134). Similar results were found by Nash et al, showing a success rate of 77.3% for the 22 patients who were explanted and re‐implanted compared to a success rate of 80.9% for the entire cohort (N = 68).…”
Section: Discussionsupporting
confidence: 87%
“…Long‐term failures were primarily attributed to device leakage. Recent studies have shown that the results of reimplantation are comparable to the results after the first implantation . Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions .…”
Section: Discussionmentioning
confidence: 97%
“…29 Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al 20 19,30 Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions. 31 For those individuals whose incontinence does not improve with ProACT therapy, this minimally invasive treatment can be easily reversed without hindering implantation of a more invasive therapy, such as AUS.…”
Section: Discussionmentioning
confidence: 97%
“…However, the patient baseline characteristics were not always comparable since these studies also included a population of patients with SUI related to transurethral resection of the prostate 16,19‐21,24 . Moreover, in some series, the severity of incontinence at baseline also varies from study to study, particularly the rate of mild incontinence that can range from 3% to 56% 13,14,16,25 . The current study reports 59% of mild SUI.…”
Section: Discussionmentioning
confidence: 79%